Serum alpha-1 acid glycoprotein and gallstone risk in US adult women: a cross-sectional analysis of the NHANES - Xiaocheng Li; Peiling He (Frontiers in Nutrition)
BackgroundGallstone disease, a common biliary disorder, is linked to inflammation and immune responses. However, the association between serum alpha-1 acid glycoprotein (AGP), a key inflammatory marker, and gallstone risk remains underexplored.MethodsData from the National Health and Nutrition Examination Survey (NHANES) 2017–2020 and 2021–2023 cycles were analyzed. Gallstone disease was determined by self-reported physician diagnosis. Serum AGP levels were measured using a high-sensitivity turbidimetric immunoassay. Weighted logistic regression, subgroup analyses, smoothed curve analysis, and multiple imputation were used to examine the relationship between AGP and gallstone risk.ResultsThis cross-sectional analysis included 1,903 adult women in the U.S. aged 20–49. After adjusting for all covariates, serum AGP levels were positively associated with gallstone risk (OR: 3.07; 95% CI: 1.16, 8.11; p = 0.036). Compared to the first tertile (T1), the third AGP tertile (T3) had an OR of 1.87 (95% CI: 1.11, 3.14; p = 0.030). Smoothed curve analysis indicated a positive relationship between AGP and gallstone risk. Subgroup analyses consistently demonstrated this positive association across various demographic and clinical categories, with significant interactions observed for the ratio of family income to poverty. Sensitivity analyses using multiple imputation further supported the conclusion that AGP was associated with increased gallstone risk.ConclusionAGP is significantly associated with an increased risk of gallstones in U.S. adult women, suggesting its potential as a biomarker for risk stratification. Further research is needed to elucidate the underlying mechanisms and potential causal relationships.